Development of fish-based indices of biological integrity for Minnesota lakes - Jacquelyn Bacigalupi (Elsevier, 2021)
Indices of biological integrity (IBIs) have been developed for a wide variety of locales and ecological systems to describe their biological condition. Due to variability in geophysical and chemical conditions, IBIs are often developed regionally and applied to similar ecological systems. Researchers in Minnesota previously developed a fish IBI (FIBI) for lakes; however, its application was limited to lakes 40–200 ha surface area and located in central Minnesota. The objectives of this study were to develop FIBIs and ecologically meaningful thresholds for application to a broader suite of Minnesota lakes with surface areas 40–4,050 ha. Fish communities in 419 lakes throughout Minnesota were sampled using gill nets, trap nets, backpack electrofishers, and beach seines between mid-June and early-September 2005–2013. Fish species were assigned to functional groups based on family, tolerance, primary feeding niche, special habitat use, and whether they were native to Minnesota. Lakes were classified into seven groups based on their geophysical and chemical attributes, and four groups were ultimately used in FIBI development. A suite of potential metrics was evaluated for each of the four FIBIs based on their relationships to measures of human-induced watershed and in-lake stressors and 8–15 were retained for each FIBI. Metrics that were retained were summed, and composite scores were scaled 0–100. Biological Condition Gradient (BCG) models were developed for each FIBI. The BCG models established thresholds for impairment and exceptional condition. The FIBIs and thresholds are being used to guide clean water planning, restoration, and protection efforts and to complement pollutant-based water quality sampling efforts in lakes during the Minnesota watershed assessment process.